Anionic Synthesis of α‐Functionalized Polymers by Combination of 1, 1‐Diphenylethylene and Hydrosilation Chemistry. Issue 1 (15th April 2013) - Quirk, Roderic P.; Sahoo, Sujata
Abstract: A new general anionic functionalization method (GFM) for preparing α‐chain‐end functionalized polymers utilizes the initiator formed from sec ‐butyllithium and dimethyl[4‐(1‐phenylvinyl)‐phenyl]silane (DPESiH) followed by hydrosilation with substituted alkenes. α‐(4‐dimethylsilyl hydride)phenyl‐functionalized polystyrene and poly(methyl methacrylate) were synthesized in quantitative yield by living anionic polymerization. These α‐silyl hydride‐functionalized polymers were further functionalized by reaction with tridecafluorooctene in the present of Karstedt's hydrosilation catalyst. These tridecafluorooctane‐functionalized polymers were characterized by SEC, FTIR, 1 H‐, 13 C‐ and 19 F‐NMR spectroscopy.